Skład chemiczny roślin uprawianych na glebach pobagiennych nawożonych cynkiem i miedzią = Chemical compostion of plants grown on post-bog soils fertilised with zinc and copper - Meller, Edward; Jarnuszewski, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In pot experiments the influence of Zn and Cu fertilisation on the yield quantity and quality of the plants grown on the muck taken from 2 postbog soils on lacustrine chalk: organic muck soil and limnic-muck soil, was compared. The experiments were conducted in the years 2000-2002 and each year the pots were filled with a new muck material. The main crop included: maize (2000), spring barley (2001), spring wheat (2002); and after crop: mustard (2000), rape (2001) and oats (2002). Zinc dose was 18 mg Zn kg-1 soil dry matter and copper ? 9 mg Cu kg-1 soil dry matter.
Keywords: gleby pobagienne; nawożenie; mursz; post-bog soils; fertilization; muck